Ultrasound-guided transversus abdominis plane block using ropivacaine and dexmedetomidine in patients undergoing caesarian sections to relieve post-operative analgesia: A randomized controlled clinical trial - Qian, Haitao (Exp Ther Med, 2020)
Dexmedetomidine, which is a highly selective α2 adrenoreceptor agonist, enhances the analgesic efficacy and prolongs the analgesic duration when administered in combination with local anesthetics. The current study aimed to evaluate the effects of dexmedetomidine combined with ropivacaine in ultrasound-guided transversus abdominis plane (TAP) block on post-operative analgesia following cesarean section (CS). A total of 70 patients scheduled for CS were divided randomly into 2 groups: The ropivacaine (R) group, in which patients were administered bilateral 20 ml 0.3% ropivacaine and 2 ml 0.9% normal saline, and the dexmedetomidine (RD) group, in which patients were administered bilateral 20 ml 0.3% ropivacaine and 2 ml dexmedetomidine (0.5 µg/kg). The primary outcome was pain-free duration, and secondary outcomes included heart rate (HR) and mean blood pressure (MBP) measurements, visual analogue scale (VAS) pain scores, number of patients who required rescue analgesic, time to first request for analgesia and patient satisfaction. There was no significant difference in HR and MBP between the two groups at 1 h post-surgery (P>0.05). However, VAS pain scores decreased at 6 and 8 h post-surgery [2 (1-2) vs. 0 (0-0.25) and 2 (2-3) vs. 0 (0-1), respectively; P<0.05], pain-free duration was prolonged (5.91±1.08 vs. 9.62±1.46 h; P<0.05), the number of patients who required rescue analgesic was reduced (19 vs. 9; P<0.05), the time to first request for analgesia was prolonged (7.10±1.21 vs. 11.60±2.11 h; P<0.05) and patient satisfaction was improved [3.5 (3-4) vs. 4 (4-5); P<0.05] in the RD group compared with the R group. Furthermore, no bradycardia or hypotension was observed. In conclusion, the results of the present study demonstrated that adding 0.5 µg/kg dexmedetomidine to 0.3% ropivacaine used in TAP block in patients undergoing CS prolonged pain-free duration, decreased VAS pain scores, reduced the number of patients who required rescue analgesic, prolonged the time to first request for analgesia and improved the patient satisfaction without serious side effects.